Climber Prospective Teacher: Relationship Beliefs and Mathematics Teaching Practice - Muhtarom, Muhtarom; Siswono, Tatag Yuli Eko; Juniati, Dwi (Universitas Islam Raden Intan Lampung, INDONESIA, 2020)
This research explained the description of the beliefs of prospective teacher who had an adversity quotient type climber and the relationship between beliefs and mathematics teaching practices in the classroom. One student of climber prospective teacher who had taken an internship course and had good communication skill was willing to become a research subject. Semi-structured interview and observation of learning in class were used to obtain the research data. The data that had been obtained were coded, reduced, presented, triangulated to obtain credible data, and then conclusions were drawn. The results show that the climber math prospective teacher believes that mathematics is as something dynamic, namely the space of creation, human invention that develops continuously. Teaching mathematics is student-centered through problem providing or problem solving, and learning is as a construction of student’s active understanding to build knowledge. A more detailed explanation of beliefs description and the relationship with the mathematics teaching practice is described in this research.